THE ANALYSIS OF USING TV (THEMATIC VOCABULARY) CARDS IN INCREASING THE STUDENTS’ ENGLISH VOCABULARY - Rahmati; Helmiyadi Helmiyadi (English Education Department, 2021)
This study aims to determine whether Thematic Vocabulary (TV) Cards media can improve the vocabulary of students in primary school. In order to achieve the objectives of the study, the researcher designed an action research which consisted of pre-test, 3 cycles of treatment, and post-test. The subject of this study was the students of SMK N 1 Lhokseumawe, with the number of the subject was 26 students; 9 males and 17 females. 2 meetings were held during the research in which the students had to join test and also cycles of treatment which consisted of quizzes and various activities by using TV Cards as the media. which used the Sugiyono’s model (2016:298) with adaptation. The data collecting through interview, questionnaire, documentation, and test. The result of this study showed there was a significant improvement made by the students in identifying and remembering new English vocabulary available in the given descriptive texts. Pre- test result showed 27 % of students scored less than 50; 69 % students scored 51- 75; and only the rest of them scored more than 76, meaning that the average score of the class was still low, which was only 54.10. After conducting Post- test, it could be seen that no student scored less than 50; only one student scored 73; and the rest of them successfully scored above 76. Compared to Pre- Test’s result, the Post- Test’s showed the better average score, which increased up to 79%. In line with the result, Some suggestions are offered for teachers to be a facilitator in creating effective learning activities, to be able to make teaching and learning process more interesting, enjoyable and educative.